Nursing care plans : - Gulanick, Meg (Elsevier/Mosby, 2014)
The bestselling nursing care planning book on the market, Nursing Care Plans: Diagnoses, Interventions, and Outcomes, 8th Edition covers the most common medical-surgical nursing diagnoses and clinical problems seen in adults. It includes 217 care plans, each reflecting the latest evidence and best practice guidelines. NEW to this edition are 13 new care plans and two new chapters including care plans that address health promotion and risk factor management along with basic nursing concepts that apply to multiple body systems. Written by expert nursing educators Meg Gulanick and Judith Myers, this reference functions as two books in one, with 147 disorder-specific and health management nursing care plans and 70 nursing diagnosis care plans to use as starting points in creating individualized care plans.